2013
DOI: 10.1016/j.gie.2013.03.1334
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fair colonoscopy preparation on colonoscopy use and adenoma miss rates in patients undergoing outpatient colonoscopy

Abstract: Background The impact of fair bowel preparation on endoscopists’ recommendations and adenoma miss rates in average-risk patients undergoing colonoscopy is unknown. Objective To assess the impact of fair bowel preparation on endoscopists’ interval colonoscopy recommendations and miss rates in colonoscopies performed within 3 years of the index colonoscopy in average-risk patients undergoing colorectal cancer screening. Design Retrospective chart review. Setting Tertiary-care center. Patients Average-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 26 publications
3
60
0
1
Order By: Relevance
“…Although adequate bowel preparation was seen in 91% of patients, rate of fair colon preparation was considerably high (46%). Since recently published study has shown the detrimental effect of fair bowel preparation on the rate of missing colonic adenoma (Menees et al, 2013), our study has confirmed the existence of bowel preparation quality problem of in this region.…”
Section: Discussionsupporting
confidence: 85%
“…Although adequate bowel preparation was seen in 91% of patients, rate of fair colon preparation was considerably high (46%). Since recently published study has shown the detrimental effect of fair bowel preparation on the rate of missing colonic adenoma (Menees et al, 2013), our study has confirmed the existence of bowel preparation quality problem of in this region.…”
Section: Discussionsupporting
confidence: 85%
“…Th e BBPS was signifi cantly higher in the WE group than in the AI group, suggesting that WE further enhanced BBPS even in patients receiving split-dose preparation. Inadequate and fair bowel preparation had been associated with increased miss rates of adenoma detection ( 43,44 ).…”
Section: Air Insufflation Vs Water Immersion and Exchangementioning
confidence: 99%
“…Among them, colonoscopy stands out because of its high sensitivity; it allows complete visualization of the colonic mucosa, facilitating the detection and removal of polyps, and biopsies for cancer screening (9) . According to the 1993 United States National Polyp Study, colonoscopic polypectomy reduced the incidence of CRC by 76 to 90 percent (23) . Since 1997, the American Gastroenterological Association has recommended screening for all asymptomatic individuals, aged 50 or older, with no family history of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…These individuals are in the medium-risk group (9) . Despite its obvious advantages, colonoscopy has its limitations: adequacy of intestinal preparation, risks related to sedation, the risk of perforation, the risk of missing neoplasia, and high cost (23) . For lesions smaller than 10 mm, the "miss rates" can reach 11% and the rate of inadequate colon preparation reaches 25% (5) .…”
Section: Introductionmentioning
confidence: 99%